Geochemical kinetics - Zhang, Youxue, 1957- (Princeton University Press, 2008)
"This book offers a comprehensive exploration of geochemical kinetics - the application of chemical kinetics to geological problems, both theoretical and practical. Geochemical Kinetics balances the basic theories of chemical kinetics with a thorough examination of advanced theories developed by geochemists, such as nonisothermal kinetics and inverse theories, including geochronology (isotopic dating), thermochronology (temperature-time history), and geospeedometry (cooling rates). The first chapter provides an introduction and overview of the whole field at an elementary level, and the subsequent chapters develop theories and applications for homogeneous reactions, mass and heat transfer, heterogeneous reactions, and inverse problems." "Most of the book's examples are from high-temperature geochemistry, with a few from astronomy and environmental sciences. Appendixes, homework problems for each major section, and a lengthy reference list are also provided. Readers should have knowledge of basic differential equations, some linear algebra, and thermodynamics at the level of an undergraduate physical chemistry course. Geochemical Kinetics is a resource for anyone interested in the mathematical treatment of geochemical questions."--Jacket